Association between perceived risk of harm and self-reported binge drinking, cigarette smoking, and marijuana smoking in young adults. Issue 4 (8th June 2021) - Hanauer, Matthew; Walker, Madison R.; Machledt, Kendall; Ragatz, Melissa; Macy, Jonathan T.
Abstract: Objectives: Evaluate the association between perceived risk of harm and self-reported binge drinking, cigarette smoking, and marijuana smoking among college students. Participants: Participants were 599 students (ages 19–28) at a large Midwestern university recruited from October 2015 to December 2017. Methods: Hurdle regression was used to test the relationship between perceived risk of harm from substance use (i.e., binge drinking, cigarette smoking, and marijuana smoking), and self-reported use. Demographic characteristics were tested as moderators of this relationship. Results: Engagement in all three substance use behaviors was less likely when perceived risk was high. Age moderated the association between perceived risk and self-reported marijuana smoking with younger participants demonstrating a stronger relationship between perceived risk of smoking marijuana and self-reported marijuana smoking. Conclusion: Intervention programs will be most effective when perceived risk of substance use is high. Therefore, intervention programs should aim to increase college students' perceived risk of substance use.